CLIENT EXPECTATION FROM RESIDENTIAL PROPERTY DESIGN SERVICES AND ARCHITECTS’ PERCEPTION - Adedapo Adewunmi, OLUWATAYO (DIMENSI (Journal of Architecture and Built Environment), 2013)
Very few studies exist on the expectations of clients from architects. There are however, anecdotal evidences that architects may not fully grasp what is most important to their clients. As a pilot study, the aim of this paper was to investigate the expectations of clients from residential design services and architects’ perceptions of those expectations. A questionnaire was designed to suit the purpose of comparison of responses of the two groups. The factor analysis conducted revealed that the expectations from design services could be described in terms of value, professionalism, and empathy. Using mean gap analysis, the study identified areas where architects have under-estimated the expectations of clients as well as those areas where the expectations have been over-estimated. The results would help architects to focus on areas, which are important to the clients and possibly reduce client dissatisfaction. This is study, which is one of the first on the subject, is limited in three ways. First, residential clients were the only ones considered. In addition, respondents were only taken from Nigeria and the sample size as well as the response rate was small.